Adaptation to Climate Change in Viticulture: The Role of Varietal Selection—A Review - Miguel Baltazar; Isaura Castro; Berta Gonçalves (Plants)
Viticulture faces unprecedented challenges due to the rapidly changing climate, particularly in regions like the Mediterranean Basin. Consequently, climate change adaptation strategies are crucial in viticulture, with short-term strategies being widely used despite increasing concerns about their sustainability, and long-term strategies considered promising, though costly. A promising but understudied strategy is varietal selection, as grapevines exhibit vast intervarietal diversity with untapped potential for climate-resilient varieties. By integrating research across plant physiology, biochemistry, histology, and genetics, we can better understand the traits behind the grapevine’s capability for adaptation. Several traits, including morphological, physiological, and molecular aspects, have been shown to be crucial in adapting to environmental stresses such as drought and heat. By studying the abundant grapevine intervarietal diversity, the potential for viticulture adaptation to climate change through varietal selection is immense. This review article focuses on the potential of varietal selection in the adaptation of viticulture to climate change. For this, we will delve into the research regarding how climate affects grapevine growth and grape quality and how the grapevine responds to stress conditions, followed by a summary of different climate change adaptation strategies of viticulture. Finally, we will focus on varietal selection, discussing and summarizing different studies surrounding grapevine variety behaviour.